Zintl Phases Principles and Recent Developments - Fässler, Thomas F. (Structure and Bonding, 2011)
Gordon J. Miller, Michael W. Schmidt, Fei Wang, Tae-Soo You: Quantitative Advances in the Zintl-Klemm Formalism Jürgen Evers: High Pressure Investigations on AIBIII Zintl Compounds (AI = Li to Cs; BIII = Al to Tl) up to 30 GPa Andrei Shevelkov, Kirill Kovnir: Zintl Clathrates Ulrich Häussermann, Verina F. Kranak, Kati Puhakainen: Hydrogenous Zintl Phases: Interstitial versus Polyanionic Hydrides.